PENERAPAN METODE PROMETHEE II PADA PENERIMA BANTUAN SISWA KURANG MAMPU - Fajri Fadhila; Frandito Apriansyah; Dewa Fadillah Reyzaki; Ika Melinia Sapitri (UNIVERSITAS STEKOM, 2022)
PIP is a program created to help students from low-income families to continue to receive educational services until they graduate from secondary education. The problem that often occurs is that there are underprivileged students who are not listed as recipients of the aid or scholarship. The purpose of this study was to apply the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE II) in the case of underprivileged students who received assistance. PROMETHEE II is a method of sorting or prioritizing in multi-criteria analysis, namely a decision-making technique from several choices.